THE DEVELOPMENT OF MATHEMATICAL THINKING THROUGH ADAPTIVE EDUCATION: THE CASE OF A LINEAR ALGEBRA COURSE - Díez-Fonnegra, Carlos Alberto; de Losada, Maria Falk (VIDYA, 2022)
The one-size-fits-all model is widely used in teaching and learning processes around the world. This model does not recognize students’ learning conditions and preferences. As an alternative, the adaptive education model has been developing in recent years. In mathematics, the current state of this adaptive education model is oriented to the learning of objects and algorithms and not to the development of mathematical thinking. To overcome this shortcoming, the design-based research approach was used to create and implement an adaptive learning management system framed in a module of a linear algebra course, in which adaptation was done based on modes of thinking (SIERPINSKA, 2000). The results of this implementation show that people manifest diverse modes of thinking when conceiving mathematical objects and that these modes affect the way they learn. These results also highlight some existing limitations for adaptive educational processes such as these to generate greater impacts.